1990
DOI: 10.1172/jci114780
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide in human nasal mucosa.

Abstract: Vasoactive intestinal peptide (VIP), which is present with acetylcholine in parasympathetic nerve fibers, may have important regulatory functions in mucous membranes. The potential roles for VIP in human nasal mucosa were studied using an integrated approach. The VIP content of human nasal mucosa was determined to be 2.84±0.47 pmol/g wet weight (n = 8) by RIA. VIP-immunoreactive nerve fibers were found to be most concentrated in submucosal glands adjacent to serous and mucous cells. 125I-VIP binding sites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 36 publications
1
56
0
7
Order By: Relevance
“…The tissue concentrations of VIP vary by anatomic site and disease condition but can enter a range (3,20,62) that we show herein is also able to activate the HCMV MIE genes in the NT2 cell model (Fig. 1).…”
Section: Discussionmentioning
confidence: 64%
“…The tissue concentrations of VIP vary by anatomic site and disease condition but can enter a range (3,20,62) that we show herein is also able to activate the HCMV MIE genes in the NT2 cell model (Fig. 1).…”
Section: Discussionmentioning
confidence: 64%
“…In this respect, the present study was carried out cautiously to reach the highest standards of reproducibility and stringency. The 28-amino acid peptide VIP was first isolated from small intestine and lung as a vasodilatory peptide [32] and is one of the most abundant neuropeptides found in human nasal mucosa [33,34]. Although there are no reports on the effects of nasally-administered VIP in humans, it is generally accepted that VIP plays a major role in the upper respiratory tract and influences many aspects of airway function [35] due to its role as a neuromodulator of the inhibitory nonadrenergic noncholinergic nervous system [36].…”
Section: Discussionmentioning
confidence: 99%
“…The inferior nasal turbinates are rich in submucosal glands, which secrete copious amounts of fluid and mucus to humidify inspired air and trap particles and pathogens. Functional and histological studies have not revealed any significant differences between nasal submucosal glands and those found in lower airways (16,(33)(34)(35)(36)(37), and intact human nasal glands also exhibit CFTR-dependent fluid secretion in response to [cAMP] i -elevating agonists (16,37).…”
Section: Low [Vip] Potentiates Cftr-dependentmentioning
confidence: 97%